Sociological Study of Women's Reproductive Health in Almaty: Determinants and Diseases - А. Бакытжанова; Г. Алимбекова; П. Власенко (Хабаршы. Психология және социология сериясы)
This article presents the results of a sociological study aimed at studying the state of women's reproductive health in Almaty and identifying the factors influencing it. The main objective of the study is to analyze the socio-economic and socio-cultural determinants that determine the level of access to health services and awareness of women of reproductive age about preventive measures and disease risks. Particular attention is paid to the issues of accessibility and quality of health care, awareness of contraception and prevention methods, as well as the influence of existing cultural stereotypes on women's behavioral attitudes in the field of health.